2020
DOI: 10.1002/jrs.5823
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sensitive detection of pesticide residues using dynamic surface‐enhanced Raman spectroscopy

Abstract: Pesticide residues are one of the major food safety concerns for consumers all over the world, and it is crucial to develop simple, rapid, and effective method for the detection of pesticide residues. In the study, we report the sensitive detection of pesticides with the dynamic surface‐enhanced Raman spectroscopy (dynamic SERS) method. The dynamic SERS method provides excellent detection sensitivity at the metastable state of plasmonic nanoparticles in the sessile drop, which is a critical state between the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The characteristic strong or very strong peaks around 627 cm -1 (Á < -3 cm -1 ), 817 cm -1 (Á < AE2 cm -1 ), and 1096 cm -1 (Á < AE3 cm -1 ) can be assigned to the stretching C-Cl vibration. 10 All peaks in the SERS spectra have very small shifting with respect to those reported. 9,10,12 Furthermore, according to Cañamares and Feis 12 and Yaseen et al, 14 the bands observed by us around 817 and 1585 cm -1 can be connected with CH bending and pyridine stretching bands, respectively.…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 73%
See 2 more Smart Citations
“…The characteristic strong or very strong peaks around 627 cm -1 (Á < -3 cm -1 ), 817 cm -1 (Á < AE2 cm -1 ), and 1096 cm -1 (Á < AE3 cm -1 ) can be assigned to the stretching C-Cl vibration. 10 All peaks in the SERS spectra have very small shifting with respect to those reported. 9,10,12 Furthermore, according to Cañamares and Feis 12 and Yaseen et al, 14 the bands observed by us around 817 and 1585 cm -1 can be connected with CH bending and pyridine stretching bands, respectively.…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 73%
“…10 All peaks in the SERS spectra have very small shifting with respect to those reported. 9,10,12 Furthermore, according to Cañamares and Feis 12 and Yaseen et al, 14 the bands observed by us around 817 and 1585 cm -1 can be connected with CH bending and pyridine stretching bands, respectively. Additionally, these peaks are consistent with the Raman peaks taken when the chemical was deposited on the glass substrate (Table II).…”
Section: Surface-enhanced Raman Spectroscopymentioning
confidence: 73%
See 1 more Smart Citation
“…It is a significant criterion for the developed SERS sensor to achieve sensitive detection signals. The Raman signals of the SERS sensor change with the increase of the volatilization amount of the sessile droplet of SiO 2 @Ag nanoparticles and target species, and the most effective enhancement of signals takes place with the self-aggregation of the SiO 2 @Ag nanoparticles to the external ring during the solvent evaporation owing to the coffee ring effect. , To overcome the influence of the coffee ring effect during the dynamic process, the evolution intensities of the SERS signals were recorded for paraquat with a concentration of 10 –3 mol·L –1 to obtain the optimum detection conditions on the coffee ring and the non-coffee ring, as summarized in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Many researchers have successfully used the Raman spectrometry method to detect pesticide residues based on SERS using noble nanometals, especially gold nanostructures for controlling pollution of fruits and food. [10,11] Since being accidentally discovered in 1956 by Arthur Uhlir and Ingeborg Uhlir, porous silicon (PSi) has been widely used for sensors, such as biological sensors, [12,13] electrochemical sensors, [14] and optical sensors. [15] PSi exhibits key features for label-free sensors and biochemical sensor applications due to its easy, fast, and low-cost fabrication; tunable shape, pore size, porosity, and thickness [16] ; high surface area of %170 m 2 cm À3 [17] ; detection of molecules/ target analytes via the photoluminescent spectrum or as a wavelength shift in the reflectivity spectrum; and biocompatibility with existing silicon-based microelectronic technology for biological applications.…”
Section: Surface-enhancedmentioning
confidence: 99%